2003
DOI: 10.1097/00043426-200306000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Interleukin-1 Receptor Antagonist and Tumor Necrosis Factor-Alpha Are Elevated in Children With Langerhans Cell Histiocytosis

Abstract: Patients with LCH have elevated levels of IL-1Ra and TNF, which decrease after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…We have previously reported that pretreatment serum levels of TNF-␣, sIL-2R, and IL-1Ra are elevated in LCH (11,22). Similarly, in the present study, these immunomodulating cytokines were highly expressed in LCH patients at the time of onset of disease; moreover, a significant positive correlation was observed between TNF-␣ and OPG serum concentrations, at the time of diagnosis.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…We have previously reported that pretreatment serum levels of TNF-␣, sIL-2R, and IL-1Ra are elevated in LCH (11,22). Similarly, in the present study, these immunomodulating cytokines were highly expressed in LCH patients at the time of onset of disease; moreover, a significant positive correlation was observed between TNF-␣ and OPG serum concentrations, at the time of diagnosis.…”
supporting
confidence: 85%
“…We have previously shown that pretreatment serum levels of soluble IL-2 receptor (sIL-2R), IL-1 receptor antagonist (IL-1Ra), and TNF-␣ are elevated in children with LCH (11,22). In the present study, we analyzed serum levels of these cytokines in LCH patients at the time of diagnosis [TNF-␣ (n ϭ 9), sIL-2R (n ϭ 12), IL-1Ra (n ϭ 11)] as well as in pediatric controls (n ϭ 14 for TNF-␣ and sIL-2R measurements, and n ϭ 7 for IL-Ra measurements).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations